2008
DOI: 10.1007/s00213-008-1320-7
|View full text |Cite
|
Sign up to set email alerts
|

Positive effects of nicotine on cognition: the deployment of attention for prospective memory

Abstract: The present study suggests that nicotinic stimulation does not work to enhance perceptual salience of target stimuli (experiment 2), nor does it work through better deployment of preparatory working attention (experiment 1). An alternative explanation that nicotine promotes PM detection by facilitating disengagement from the ongoing task is suggested as a future line of investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
1
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 45 publications
2
27
1
6
Order By: Relevance
“…The facilitative effect of nicotine on PM was observed here on timebased but not event-based tasks. This is in contrast to Rusted's group (Rusted et al 2005(Rusted et al , 2009Rusted and Trawley 2006) who have not included time-based tasks but who have found improvements with nicotine on event-based PM, and with Jansari et al (in press) who found effects of nicotine gum on both event-and time-based tasks with comparable effect sizes. That differences have emerged between these studies is not surprising given the different methods of nicotine administration and heterogeneous PM tasks employed which vary in the extent to which they engage strategic processing.…”
contrasting
confidence: 84%
See 1 more Smart Citation
“…The facilitative effect of nicotine on PM was observed here on timebased but not event-based tasks. This is in contrast to Rusted's group (Rusted et al 2005(Rusted et al , 2009Rusted and Trawley 2006) who have not included time-based tasks but who have found improvements with nicotine on event-based PM, and with Jansari et al (in press) who found effects of nicotine gum on both event-and time-based tasks with comparable effect sizes. That differences have emerged between these studies is not surprising given the different methods of nicotine administration and heterogeneous PM tasks employed which vary in the extent to which they engage strategic processing.…”
contrasting
confidence: 84%
“…It is possible, however, that nicotine may confer a benefit over and above a reversal of deprivation-associated deficits as is suggested by facilitative effects of nicotine in minimally (2hr) deprived smokers and non-smokers (Rusted and Trawley 2006;Rusted et al 2009). Ascertaining such a 'true' facilitative effect of nicotine was beyond the scope of this study but it would be interesting to determine whether nicotine derived via the e-cigarette can improve PM in non-smokers and potentially offer another pharmacological intervention to promote cognitive functioning in older adults.…”
mentioning
confidence: 99%
“…Participants first completed this task before drug administration as a measure of 'decisionmaking' ability. They were instructed to sort a deck of 52 playing cards according to suit (Rusted et al, 2009). Each card image remained on the computer screen for 750 ms with an ISI of 1000 ms (in which the back of a playing card was displayed).…”
Section: Neuropsychological Assessmentmentioning
confidence: 99%
“…The Digit Symbol Substitution Task (DSST, Wechsler, 1981) Trail Making Test A and B (Reitan, 1958) Controlled Oral Word Association Test (COWAT, Spreen & Strauss, 1991) 20-Word Item Episodic Memory Task (Rusted & Warburton, 1989) Backward Digit Span (Wechsler, 1981) Prospective and Retrospective Memory Questionnaire (PRMQ; Crawford, Smith, Maylor, Della Sala, & Logie, 2003) Prospective Memory Card Sort Task (Rusted, Sawyer, Jones, Trawley, & Marchant, 2009) Focal and Non-Focal Prospective Memory Task (McDaniel et al, 2011) Map Test of Everyday Attention (Robertson, Ward, Ridgeway, & Nimmo-Smith, 1996) Rapid Visual Information Processing (RVIP; Wesnes & Warburton, 1983) Stroop-Switch Task (Hutchison et al, 2010) …”
Section: Cognitive Tasksmentioning
confidence: 99%
“…Card Sort Task (Rusted et al, 2009) Participants sorted playing cards into hearts and spades, while ignoring diamonds and clubs. The non-focal PM intention was to press the spacebar for number 7 cards regardless of suit.…”
Section: Event-based Pm Tasksmentioning
confidence: 99%